2001
DOI: 10.1210/jcem.86.11.8033
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Maternal Nicotine Exposure Alters Neuronal Systems in the Arcuate Nucleus That Regulate Feeding Behavior in the Newborn Rhesus Macaque

Abstract: It is well known that maternal smoking during pregnancy can lead to low birth weight and low body fat in human newborns. The purpose of this study was to determine whether chronic maternal nicotine treatment alters levels of known regulators of energy balance in the newborn offspring. Pregnant rhesus monkeys were treated with nicotine tartrate (1.5 mg/kg x d) starting on d 26 of pregnancy and maintained through d 160 of gestation. Nicotine exposure had no significant effect on absolute birth weights of the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 54 publications
3
34
0
Order By: Relevance
“…15 This observation indicates that maternal smoking in pregnancy may also be an independent risk factor for overweight in children at school entry, as it has been suggested to affect the appetite regulation system in the developing brain. 55,56 The association between maternal education and childhood overweight at 3-5 years of age observed in the present study accords with the findings from other similar studies. 15,46,57,58 In all these studies preschoolers born to mothers having a higher education (usually with a college or a university degree) were less likely to be overweight than children born to mothers with lower education (usually with a junior high school degree).…”
Section: Discussionsupporting
confidence: 93%
“…15 This observation indicates that maternal smoking in pregnancy may also be an independent risk factor for overweight in children at school entry, as it has been suggested to affect the appetite regulation system in the developing brain. 55,56 The association between maternal education and childhood overweight at 3-5 years of age observed in the present study accords with the findings from other similar studies. 15,46,57,58 In all these studies preschoolers born to mothers having a higher education (usually with a college or a university degree) were less likely to be overweight than children born to mothers with lower education (usually with a junior high school degree).…”
Section: Discussionsupporting
confidence: 93%
“…1). A previous study reported birth weight adjusted for maternal weight as about 2% less with smoke exposure (Grove et al, 2001). This was also the case in the present sample.…”
Section: Resultssupporting
confidence: 87%
“…20,69 In animal studies, administration of nicotine to pregnant mothers resulted in offspring that were smaller at birth but had increased body fat. [70][71][72][73] In other studies, rats prenatally exposed to low doses of nicotine were not smaller at birth but became heavier by 5-10 weeks of age 74,75 and had higher overall body fat as well as increased perivascular adipose tissue, resulting in decreased vascular relaxation. 75 In another protocol, prenatal nicotine exposure did not influence body weight, but caused higher blood pressure only among genetically susceptible rats.…”
Section: Discussionmentioning
confidence: 89%